Chasing Mavericks - Apted, Michael; Hanson, Curtis; Johnson, Mark; Hooper, Brandon; Meenaghan, Jim; Salem, Kario; Butler, Gerard, 1969-; Weston, Jonny; Shue, Elisabeth; Spencer, Abigail; Rambin, Leven; Fischer, Chad; et al. (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 2013)
"When 15-year-old Jay Moriarty (Weston) discovers that the mythical Mavericks surf break is real, he reaches out to local surfing legend Frosty Hesson (Butler) to train him to ride it. What begins as a mentorship turns into an extraordinary bond that transforms both their lives, as Jay and Frosty learn valuable lessons about conquering fear in pursuit of your dreams"--Container.
Originally produced as a motion picture in 2012.
Bonus features: theatrical feature ; Live like Jay ; Surfer Zen ; audio commentary with Michael Apted, Brandon Hooper and Jim Meenaghan ; theatrical trailer ; sneak peek.
Director of photography, Bill Pope ; editor, John Gilbert ; music, Chad Fischer ; story by Jim Meenaghan & Brandon Hooper.
Gerard Butler, Jonny Weston, Elisabeth Shue, Abigail Spencer, Leven Rambin.
MPAA rating: PG; for thematic elements and some perilous action.
DVD, NTSC, region 1, dual-layer, widescreen presentation; Dolby Digital 5.1.
Keywords: Moriarity, Jay -- Drama; Surfers -- Drama; California -- Drama; DVDs; Sports films; Drama; Feature films; Fiction films; Video recordings for people with visual disabilities; Video recordings for the hearing impaired